Genetics and epigenetics of fetal alcohol spectrum disorders - Feng C Zhou (Frontiers Research Topics, 2015)
Women drinking during pregnancy can result in Fetal Alcohol Spectrum Disorder (FASD), which may feature variable neurodevelopmental deficits, facial dysmorphology, growth retardation, and learning disabilities. Research suggests the human brain is precisely formed through an intrinsic, genetic-cellular expression that is carefully orchestrated by an epigenetic program. This program can be influenced by environmental inputs such as alcohol. Current research suggests the genetic and epigenetic elements of FASD are heavily intertwined and highly dependent on one another. As such, now is the time for investigators to combine genetic, genomic and epigenetic components of alcohol research into a centralized, accessible platform for discussion. Genetic analyses inform gene sets which may be vulnerable to alcohol exposure during early neurulation. Prenatal alcohol exposure indeed alters expression of gene subsets, including genes involved in neural specification, hematopoiesis, methylation, chromatin remodeling, histone variants, eye and heart development. Recently, quantitative genomic mapping has revealed loci (QTLs) that mediate alcohol-induced phenotypes identified between two alcohol-drinking mouse strains. One question to consider is (besides the role of dose and stage of alcohol exposure) why only 5% of drinking women deliver newborns diagnosed with FAS (Fetal Alcohol Syndrome)? Studies are ongoing to answer this question by characterizing genome-wide expression, allele-specific expression (ASE), gene polymorphisms (SNPs) and maternal genetic factors that influence alcohol vulnerability. Alcohol exposure during pregnancy, which can lead to FASD, has been used as a model to resolve the epigenetic pathway between environment and phenotype. Epigenetic mechanisms modify genetic outputs through alteration of 3D chromatin structure and accessibility of transcriptional machinery. Several laboratories have reported altered epigenetics, including DNA methylation and histone modification, in multiple models of FASD. During development DNA methylation is dynamic yet orchestrated in a precise spatiotemporal manner during neurulation and coincidental with neural differentiation. Alcohol can directly influence epigenetics through alterations of the methionine pathway and subsequent DNA or histone methylation/acetylation. Alcohol also alters noncoding RNA including miRNA and transposable elements (TEs). Evidence suggests that miRNA expression may mediate ethanol teratology, and TEs may be affected by alcohol through the alteration of DNA methylation at its regulatory region. In this manner, the epigenetic and genetic components of FASD are revealing themselves to be mechanistically intertwined. Can alcohol-induced epigenomic alterations be passed across generations? Early epidemiological studies have revealed infants with FASD-like features in the absence of maternal alcohol, where the fathers were alcoholics. Novel mechanisms for alcohol-induced phenotypes include altered sperm DNA methylation, hypomethylated paternal allele and heritable epimutations. These studies predict the heritability of alcohol-induced epigenetic abnormalities and gene functionality across generations. We opened a forum to researchers and investigators the field of FASD to discuss their insights, hypotheses, fresh data, past research, and future research themes embedded in this rising field of the genetics and epigenetics of FASD. This eBook is a product of the collective sharing and debate among researchers who have contributed or reviewed each subject.